2012
DOI: 10.1016/j.bios.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the detection limits: The evanescent field in surface plasmon resonance and analyte-induced folding observation of long human telomeric repeats

Abstract: Conventional analysis of molecular interactions by surface plasmon resonance is achieved by the observation of optical density changes due to analyte binding to the ligand on the surface. Low molecular weight interaction partners are normally not detected. However, if a macromolecule such as DNA can extend beyond the evanescent field and analyte interaction results in a large-scale contraction, then the refractive index changes due to the increasing amount of macromolecules close to the surface. In our proof-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Experiments with CZ-1 cells derived from multiple myeloma patients further confirmed that the static level of IL-6 was indeed upregulated upon BTZ treatment ( Figure 6B). Previously, it was proposed that multiple myeloma cells could adhere to bone marrow stromal cells and trigger them to secret IL-6, a key inflammatory cytokine that mediates growth signaling in various cancer lines [68,69]. Upregulation of IL-6 signaling by BTZ treatment might confer growth advantage in multiple myeloma cells [70].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with CZ-1 cells derived from multiple myeloma patients further confirmed that the static level of IL-6 was indeed upregulated upon BTZ treatment ( Figure 6B). Previously, it was proposed that multiple myeloma cells could adhere to bone marrow stromal cells and trigger them to secret IL-6, a key inflammatory cytokine that mediates growth signaling in various cancer lines [68,69]. Upregulation of IL-6 signaling by BTZ treatment might confer growth advantage in multiple myeloma cells [70].…”
Section: Discussionmentioning
confidence: 99%
“…As G4s can form high affinity interactions with otherwise separate oligonucleotide strands, other high molecular weight approaches in sensing and actuation have been explored. For instance, the potassium-dependent contraction of a long human telomeric repeat sequence was observed by surface plasmon resonance (SPR) that could measure the change of mass within its evanescent field [101]. Technically, fluorescence energy transfer (FRET) can be used to directly measure the structural change but with the disadvantage of using labels, or by direct probing using atomic force microscopy.…”
Section: G-quadruplex-based Detection Systemmentioning
confidence: 99%
“…In contrast, using this principle of SPR, an on-line and direct measurement of structural change can be performed without the need of labels. The changes in refractive index resulting from the binding events or in the structure of biomolecules such as RNA are able to be measured too [101]. Thus, it may be possible to detect interactions that influence the formation of G4s by mere mechanical means.…”
Section: G-quadruplex-based Detection Systemmentioning
confidence: 99%
“…This consequently leads to the generation of more plasmons, resulting in enhanced sensitivity. Thus, in this present work, we use nanosized monolayers of graphene and WS 2 for enhanced sensing of biomolecular interactions. ,, …”
Section: Introductionmentioning
confidence: 99%